Optimization of VFD Operations for Transporting Equipment of Packages - Urmoniene, Lione; Dikun, Jelena; Januteniene, Jolanta (Elektronika ir Elektrotechnika, 2021)
This study is focused on the efficiency of automated transferring system of packages equipped by variable-frequency drive (VFD) and servo drive motor. It was found that rotation frequency of induction motors and linear speed of servo drive decisively affected the unit efficiency that operates in the periodic mode. The system duty cycle was divided in two separate parts taking into account time spans needed to complete the specific tasks by each separate equipment of the system. In order to reduce the power usage of the system, the duration of each part of cycle was extended. Lowered electricity consumption leads to the extension of each cycle’s stage operating times. Frequencies of motors and linear speed of servo drive motors were optimized depending on cycle stages duration. Optimized frequency and linear speed values were calculated and loaded into motors controllers, and the efficiency of each separate equipment was measured, as well as total efficiency of the system. Experimental system debugging using optimized parameters proved that system efficiency increases up to 60 %, and that is closely matched with calculated values.